Dall’Italia al Brasile: il ruolo della Santa Sede e della Curia arcivescovile di Milano nella concessione dei visti agli ebrei convertiti (1939-1941) - Bonomelli, Chiara (Rivista di storia della Chiesa in Italia, 2024)
In the last decades, historians started investigating the assistance provided during the Second World War by the Holy See to the persecuted Jews. This work is intended as part of this historiographical trend and focuses on the 3.000 visas granted in June 1939 by the Brazilian government upon the request of the Vatican and devoted to German Jews converted to Catholicism. We analysed the archival fond Pratiche di ebrei conserved in the Archivio Storico Diocesano of Milan, which contains dossiers sent by the archbishop of Milan to the Holy See aimed at helping Milanese Jews, both converted to Catholicism and not, as well as other funds conserved in the Vatican archives. This article highlights the inconsistences in the management of the visas by the Brazilian Government and describes a still little-known aspect of the assistance provided by the Vatican to save persecuted Jews.